Dysphania anthelmintica (Amaranthaceae), new to nonnative flora of Italy, and taxonomic considerations on the related species - Iamonico, Duilio (Hacquetia, 2015)
Dysphania anthelmintica is recorded for the first time for Italy (Lazio region). Morphological and ecological characteristics of this plant and its invasive status, as compared with those of Dysphania ambrodioides and Chenopodium suffruticosum, are presented and discussed. Taxonomical notes are also provided.